How the Bible Feels: The Christian Bible as Effective and Affective Object. Issue 1 (3rd July 2017) - Parmenter, Dorina
Abstract : Despite Christian leaders' insistence that what is important about the Bible are the messages of the text, throughout Christian history the Bible as a material object, engaged by the senses, frequently has been perceived to be an effective object able to protect its users from bodily harm. This paper explores several examples where Christians view their Bibles as protective shields, and will situate those interpretations within the history of the material uses of the Bible. It will also explore how recent studies in affect theory might add to the understanding of what is communicated through sensory engagement with the Bible.